Preparation of β-cyclodextrin-based dimers with selectively methylated rims and their use for solubilization of tetracene - Lebedinskiy, Konstantin; Lobaz, Volodymyr; Jindřich, Jindřich (Beilstein journal of organic chemistry, 2022)
A series of β-cyclodextrin dimers selectively permethylated on the primary or secondary rim with two different types of spacers have been synthesized effectively utilizing conventional and newly developed methods. Their structure analyses by 1H NMR and NOESY NMR imply the dependence of molecular symmetry on the type of spacer. The ability of synthesized dimers to increase the solubility of tetracene in DMSO was evaluated and compared to native cyclodextrins and their methylated derivatives. The newly synthesized compounds expressed better effectiveness than other tested supramolecular hosts.
Keywords: cyclodextrin; dimer; tetracene; solubilization; methylation